A recepção de O menino do pijama listrado por leitores adultos da Biblioteca Municipal de Maringá - Zotesso, Lígia Ribeiro de Souza (2011)
This dissertation relates results of the analysis of the reception of the Portuguese translation of the John Boyne's book The Boy in the Striped Pajamas (2006) by adult readers of the Reading Club Municipal Library of Maringá. The book indicates in its catalog, for its reception. However, the book was analyzed by a group of adult readers, other than that indicated in the catalog of the book. Thus, we analyze the addressing of a book directed at children and youth, but with the reception by a group of adult readers. To develop this work, we observed a meeting was held with the readers of the Maringá Municipal Library to discuss the book The Boy in the Striped Pajamas. The comments from readers were analyzed relying on Theories of Reception: Reception Aesthetics (Jauss, 1994), Theory of Aesthetic Effect (ISER, 1996, 1999a, 1999b). With this analysis, we conclude that the reception of the text has different effects for each reading public. The phase in which the reader is to receive a particular book, according to his/her age, for example, interferes in the reception. Thus, we believe that the discrepancy between the public addressed by the another and the actual public that read the book has contributed to the various criticisms to the author for, using the Holocaust as a background to the development of the narrative and language "simplified" in this book, for instance.